A new genus for the freshwater crab Potamonemus asylos Cumberlidge, 1993, (Brachyura: Potamoidea: Potamonautidae) from Cameroon, Central Africa, with a key to the genera of the Potamonautinae. Issue 11 (27th March 2019) - Cumberlidge, Neil; Ndongo, Pierre A. Mvogo; Clark, Paul F.; Daniels, Savel R.
ABSTRACT: Buea gen. nov. is established to accommodate the freshwater crab Potamonemus asylos, from south-western Cameroon, Central Africa. This new genus is defined based on molecular evidence combined with morphological characters of the mandible and the first and second gonopods. Buea asylos comb. nov. is endemic to Cameroon, and is here compared with, and distinguished from, other freshwater crabs occurring in that country. Buea gen. nov. is the fifth freshwater crab genus known from Cameroon. The removal of P. asylos from Potamonemus leaves this genus with two species, P. mambilorum and P. sachsi, both of which are illustrated here and compared with the new genus. An amended key to the Potamonautinae genera is provided. Zoobank ID (LSID) This published work and the nomenclatural acts it contains have been registered in ZooBank, the online registration system for the ICZN. The ZooBank Life Science Identifiers (LSIDs) can be resolved and the associated information viewed through any standard web browser by appending the LSID to the prefixhttp://zoobank.org/ . urn:lsid:zoobank.org:pub:5EA7E3A7-D890-45DF-B9E1-8C22131B8DF8